Mycobacterium tuberculosis PE/PPE proteins enhance the production of reactive oxygen species and formation of neutrophil extracellular traps - García-Bengoa, María; Meurer, Marita; Stehr, Matthias; Elamin, Ayssar A.; Singh, Mahavir; Oehlmann, Wulf; Mörgelin, Matthias; von Köckritz-Blickwede, Maren (Frontiers in Immunology, 2023)
Introduction Neutrophil granulocytes predominate in the lungs of patients infected with Mycobacterium tuberculosis (Mtb) in earlier stages of the disease. During infection, neutrophils release neutrophil extracellular traps (NETs), an antimicrobial mechanism by which a DNA-backbone spiked with antimicrobial components traps the mycobacteria. However, the specific mycobacterial factors driving NET formation remain unclear. Proteins from the proline-glutamic acid (PE)/proline-proline-glutamic acid (PPE) family are critical to Mtb pathophysiology and virulence. Methods Here, we investigated NET induction by PE18, PPE26, and PE31 in primary human blood-derived neutrophils. Neutrophils were stimulated with the respective proteins for 3h, and NET formation was subsequently assessed using confocal fluorescence microscopy. Intracellular ROS levels and cell necrosis were estimated by flow cytometry. Additionally, the influence of phorbol-12-myristate-13-acetate (PMA), a known NADPH oxidase enhancer, on NET formation was examined. Neutrophil integrity following incubation with the PE/PPE proteins was evaluated using transmission electron microscopy. Results For the first time, we report that stimulation of primary human blood-derived neutrophils with Mtb proteins PE18, PPE26, and PE31 resulted in the formation of NETs, which correlated with an increase in intracellular ROS levels. Notably, the presence of PMA further amplified this effect. Following incubation with the PE/PPE proteins, neutrophils were found to remain viable and structurally intact, as verified through transmission electron microscopy, indicating the occurrence of vital NET formation. Discussion These findings offer valuable insights that contribute to a better understanding of host-pathogen interactions during Mtb infection. Moreover, they underscore the significance of these particular Mtb antigens in triggering NET formation, representing a distinctive and previously unrecognized function of PE/PPE antigens.